Morphological description of the male reproductive tract of the Clymene dolphin (Stenella clymene, Gray, 1850) - Spinelli, Lucas G. [UNESP]; Randi, Caroline B. [UNESP]; Mari, Renata B. [UNESP]; Angrimani, Daniel S. R.; Carvalho, Vitor Luz; de Meirelles, Ana Carolina Oliveira; Vergara-Parente, Jociery E.; Guimarães, Juliana P. (Wiley, 2020)
Stenella clymene is an endemic species of dolphin living in tropical regions in the Atlantic Ocean. Despite its wide distribution, there is still scarce information on Stenella clymene, including its reproductive biology. In this context, this work describes the morphology of the whole male reproductive tract of the Clymene dolphin. Seven males (N = 7) were studied after stranding on the northeast coast of Brazil. The analysis was performed through the use of macroscopic techniques and light and scanning microscopy. The male reproductive system consists of large testes wrapped around the tunica albuginea and adhered to the epididymis; the testes are attached to the abdominal cavity by the mesorchium. The ductus deferens is convoluted in the proximal portion and rectilinear in the distal portion. The prostate was the only accessory gland found, which is submerged by the prostate compressor muscle and lined with a dense fibroelastic capsule. The penis is classified as fibroelastic, with a spiral sigmoid flexure associated with a large volume of muscle tissue. The penis is inserted into two vestigial bones or pelvic bones, which exhibit no connection with the spine. In conclusion, the macro- and microscopic conformation and other morphofunctional features of the male reproductive organs of Stenella clymene are in accord with the anatomy observed in other Cetartiodactyla.
Keywords: Cetacea; reproduction; Stenella clymene